Eco-Friendly Innovation Strategy: Analysis of Absorption Capacity and Knowledge Management of MSMEs in Yogyakarta - Choirunnisa, Salsadilla; Nursyamsiah, Siti (Universitas Negeri Yogyakarta, 2025)
This study aims to investigate how absorptive capacity and knowledge management affect green innovation and how the interaction between absorptive capacity and knowledge management affects green innovation, especially in the context of creative industry MSMEs in Yogyakarta. This study was designed using a purposive sampling technique. Data was collected through a survey of 100 MSMEs in the creative product industry sector in the Special Region of Yogyakarta. The research data were processed using the PLS-SEM analysis tool. The research findings indicate that absorptive capacity significantly impacts the implementation of green innovation, while knowledge management does not significantly impact the implementation of green innovation. The interaction between the company's absorptive capacity and knowledge management also does not significantly affect green innovation. The results of this study contribute to the theory and practice for MSMEs to design strategies for implementing green practices and knowledge management to enhance innovation.